Ureteral identification with indocyanine green in laparoscopic colorectal surgery. Issue 2 (23rd December 2022) - Rodríguez‐Zentner, Homero; Cukier, Moises; Montagne, Vianette; Arrue, Emmy
Abstract: Introduction: Fluorescence‐guided surgery has emerged as a complement of traditional laparoscopic surgery with the advantage that is adaptable to existent platforms. The purpose of this article is to describe our technique for ureteral identification with indocyanine green (ICG) during laparoscopic colorectal surgery. Materials and Surgical Technique: We report a case series of all patients who underwent laparoscopic colorectal surgery and ureteral injection of ICG in a private third level hospital. Results: We performed 30 laparoscopic colorectal surgeries in which we used this technique to identify the ureters. Mean age was 52.6 ± 15.28 years; 16 (53.3%) were men. The indication for surgery was diverticulitis in 18 patients. Mean urological operative time was 22.4 minutes. There were no immediate or delayed adverse effects attributable to intra‐ureteral ICG administration. Discussion: Although ureteric iatrogenic injury is uncommon, when it does happen, it significantly increases the patient's morbidity. We consider this technique has the potential to make laparoscopic surgeries safer mostly in patients with cancer, diverticular disease or endometriosis who have extensive fibrosis, adhesions, and inflammation.